FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERKELANJUTAN PENGELOLAAN PERMUKIMAN PERKOTAAN DI CISAUK - Nanang Sofwan Santosa (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2021)
Urbanization has rapidly increased urban population in Indonesia. The spread of the urban population concentrated at big cities and around 20% lived at Jabodetabek. Many urban people moved to the fringe area due to relative affordable land price. Cisauk sub district – Tangerang Regency located at Cisadane Water Catchment Area (WCA) at the fringe of Jakarta Metropolitan area has a strategic location because of a good access of transportation. The movement of people to Cisauk generates positive impacts in economic aspects such as job creation and investment and negative impacts in environment protection such as agriculture and conserved land conversion into housing and industrial area as well as decline trends of Cisadane condition due to domestic and industrial activities. This study has a purpose to understand factors that influencce sustainability of urban settlement management condition in Cisauk and its relation with the Cisadane WCA. By using MDS-Rapfish and prospective analysis method, the study shows the factors consists of switching functions of the fertile agriculture soil, development of basic infrastructures, social cohesion, population growth and its spread, and Cisadane sub WCA condition.